The Effect Of Work Environment, Work Motivation, And Training On Employee Performance At PT Sanden Intercool Indonesia - Jenny Juniantan; Pujiarti Pujiarti; Andy Andy (LPPM Universitas Buddhi Dharma, 2023)
This research was conducted to determine the effect of work environment, work motivation, and training have on employee performance at PT Sanden Intercool Indonesia. Quantitative research is the procedure used in this thesis and used questionnaires to 134 respondents. The output of data processing using SPSS 25 obtained the is 1.9781, the for the work environment is 4,392 > 1.9781, the for work motivation is 9,221 > 1.9781 and the for training is 13,026 > 1.9781. the output of the hypothesis testing found that (127.857) > (2.67) is obtained and a significance of 0.00 < 0.05 it means Work Environment, Work Motivation, and Training has an significant influence on the performance of employees of PT Sanden Intercool Indonesia.